Particularities of the output performance parameters of an engine-generator set fueled with LPG of high butane - Romero Piedrahita, Carlos Alberto; Henao Castañeda, Edison de Jesús; Mejia Calderon, Luz Adriana (Scientia et Technica, 2018)
The objective of this paper is to disclose the results of a field test protocol planned and implemented to evaluate the performance behavior of a 1200 kW engine-generator, originally operated with natural gas, converted to liquefied petroleum gas (LPG) from Cusiana oil wells in Colombia. The peculiarity of the liquefied petroleum gas from Cusiana, a byproduct in the drying process of the natural gas, is its high butane content (above 30%). For the assessment of the LPG fuel on the performance of the engine-generator set, it was coupled a resistive load bank, and instrumented for low and high speed data, and emissions. It was designed an experimental procedure that combines starting, steady state, and transient loads. The analysis focuses mainly on the quantitative and qualitative analysis of the quality of the energy generated the fuel consumption, and the developed power. In general, the engine-generator has operated normally with Cusiana LPG fuel in the state of enlistment in which it was tested, maintaining satisfactory thermal regimes. It has delivered power in a stable manner under the conditions of load according to the forecasts of its owners, although much lower than the nominal rated power advertised for natural gas. The acceleration, velocity and displacement vibration values do not exceed the limit values given by the ISO 8528-9. The operation of the engine was safe, and at no point of operation detonation was detected for the loads.